Дослідження процесу розробки компонентів графічних інтерфейсів у мобільних додатках за допомогою нейромереж - Пучка, Г. С. (ХНУРЕ, 2024)
The work considers the influence of neural networks on the development of graphical interfaces in mobile applications compared to the work of designers. The project aims to investigate the differences between interfaces created by neural networks and designers, using several well-known platforms for analysis. Neural networks, while they can automate some of the routine work, cannot completely replace designers who bring a unique style and strategic understanding to a brand. The results of the work can determine the optimal way to use neural networks in cooperation with professional designers to improve the development process of mobile interfaces.
Keywords: мобільний додаток; нейромережа